Produksi Biodiesel dari Lipid Fitoplankton Nannochloropsis sp. Melalui Metode Ultrasonik - Raymond Kwangdinata; Indah Raya; Muhammad Zakir (Hasanuddin University, 2013)
A research on production of biodiesel from lipid of phytoplankton Nannochloropsis sp. through ultrasonic extraction method has been done. In this research, we carried out a series of phytoplankton culture to determine the optimum time of growth and biodiesel synthesis process from phytoplankton lipids. Process of biodiesel synthesis consists of two steps, i.e isolation of phytoplankton lipids and biodiesel synthesis from that lipids. Oil isolation process was carried out by ultrasonic extraction method using ethanol 96 % while biodiesel synthesis was carried out by transesterification reaction using methanol and KOH catalyst under sonication. Percentage rendement of weight per biomass Nannochloropsis sp. is 48,33 %. Characterization of biodiesel was carried out in terms of physical properties: density, viscosity, and chemical properties: FFA content, saponification value, and iodine value. The result showed that analysis characterization biodiesel phytoplankton Nannochloropsis sp. that biodiesel from that species phytoplankton generally fullfilled the American Society for Testing and Materials (ASTM D6751) standard, except density value was 0,8151 g.cm-3, viscosity value was 1,15 cSt, and FFA content was 0,5381 %, to be used as fuel.